Exploratory study of the Structured Self Development experience of enlisted soldiers in the Kansas Army National Guard - Anders, Brent A. (Kansas State University, 2018)
This exploratory phenomenological research study describes the experiences of U.S. Army soldiers going through the mandated Structured Self Development (SSD) online courseware. Multiple findings are presented covering soldier participants’ experiences with the process, content, and culture/environment of SSD. Additionally, findings dealing with soldiers’ motivations and self-described impediments while going through SSD are presented. Four Army enlisted soldiers (two male, two female) were purposefully selected for this study, each one representing a different level of SSD (Levels 1-4). Participant soldiers for this study were selected from throughout the Kansas National Guard and each one possessed a different duty military occupational specialty within the Army. The findings of the research study indicate that there are multiple aspects of SSD that soldiers experienced in a negative way. Areas such as frustration with the system, cheating, poor instructional technique, low retention of information, cognitive overload, and poor leader/peer perceptions were identified through soldier participant interviews. Motivational issues dealing with negative feelings of relevancy and boredom with the instruction were also acknowledged. Additionally, difficulty in accessing the SSD system by soldiers, and over assumptions of soldiers’ levels of self-directed learning were also identified. This research contributes to the ongoing research needed dealing with soldier improvement through online learning.
Keywords: Military; Army; Structured Self Development; Online learning; Adult education